Estudio de factibilidad para la creación de una empresa de transporte dirigido a los estudiantes de la Universidad Técnica Estatal de Quevedo, año 2015 - Arroyo Zambrano, Gabriela Fernanda (2015)
This research was conducted in the canton Quevedo. Los Rios province, with the overall goal Determine a feasibility study for the creation of a transport company aimed at students of the State Technical University of Quevedo, as there is this type of service at the university. This research project will approach it in order to meet unfulfilled demand and strive to improve the quality of life of students, to no longer be exposed to danger in the different types of transportation that exist in the canton , also it generated jobs. The results obtained through the surveys of 366 students from the State Technical University of Quevedo, relevant answers could determine acceptance for conducting this research project. It was possible to determine the feasibility of the implementation of the creation of the carrier in the canton Quevedo, due to the interest of the students of this University for this type of service The budget for this project is $ 447,547.30 US dollars, which will be financed as follows, bank loan of $ 324,644.00 US dollars and the difference will be equity of each of the partners of this company. This study supports the conclusion that the project is viable; it has identified the level of acceptance of the students and the recovery of investments and costs. They managed to establish the legal and technical to be considered for the implementation of this carrier parameters financial. Keywords Feasibility, Market Study, Technical Study, Financial Study, Economic Study.